A Review of Bovine Tuberculosis in the Kafue Basin Ecosystem - Musso Munyeme; Hetron Mweemba Munang'andu (Veterinary Medicine International)
The Kafue basin ecosystem is the only remaining natural habitat for the endangered Kafue lechwe antelope (Kobus leche Kafuensis). However, hydroelectricity power production, large-scale sugar plantations, commercial fishing and increasing livestock production are threatening its natural existence and sustainability. Further, increasing human settlements within and around the Kafue basin have resulted in decreased grazing grounds for the Kafue lechwe antelopes despite a corresponding increase in cattle population sharing the same pasture. Baseline epidemiological data have persistently reported findings of bovine tuberculosis (BTB) in both wild and domestic animals, although these have been deficient in terms of describing direct evidence in the role of either lechwe antelopes or cattle in the reported observations. Despite the current literature being deficient in establishing the casual role and transmission patterns of BTB, a bimodal route of infection at the livestock/wildlife interface has been postulated. Likewise, it is not known how much of (BTB) has the potential of causing disease in humans. This paper, seeks to underline those aspects that need further research and update available data on BTB in the Kafue basin with regards to the prevalence, distribution, risk factors, threats on wildlife conservation, livestock production, public health implications, and possible mitigatory measures.